Efeito da fotobiomodulação em modelo experimental de adenocarcinoma pulmonar - Silva Neto, Edgard da (2022)
Cancer is an abnormal cell growth that invades neighboring tissues. Pulmonary adenocarcinoma (PA) is a histological subtype of lung cancer. The gold standard treatment is surgical, but most cases are diagnosed in advanced stages, preventing surgery. For this reason the search for new therapies is growing. An example is low-level laser therapy (LLLT). We evaluated the effects of photobiomodulation in an experimental model of urethane-induced lung adenocarcinoma. C57BL/6 mice were inoculated with 1g/kg intraperitoneal urethane, 2 doses with a weekly interval. After 2 weeks they underwent photobiomodulation therapy (660nm, 30mW, 3J). After euthanasia, bronchoalveolar lavage (BAL) was performed and cytokines (IL-1β, IL-6, IL-10, IFNγ and TNF-α) were quantified. The animals were separated into 4 groups: Basal (non-handled); LLLT (Irradiated with LLLT); IPA (induction of AP with urethane); IAP+LLLT (induction with urethane and irradiated with LLLT). We observed an increase in the inflammatory infiltrate in BAL in the IAP group and a decrease after photobiomodulation therapy. We found an increase in IL-6 and TNF-α levels and a reduction in IL-10 in the IAP group. After photobiomodulation therapy, we found a reduction in IL-6 and TNF-α levels and an increase in IL-10 and IFN-𝛄 in relation to the IAP group. The results together point to a possible beneficial effect of photobiomodulation therapy in reducing the number of inflammatory cells and cytokine release, decreasing the levels of IL-6 and TNF-α and increasing the levels of IL-10 and INF-γ .